Coinfections between Persistent Parasitic Neglected Tropical Diseases and Viral Infections among Prisoners from Sub-Saharan Africa and Latin America - Lilian Da Silva Santos; Hans Wolff; François Chappuis; Pedro Albajar-Viñas; Marco Vitoria; Nguyen-Toan Tran; Stéphanie Baggio; Giuseppe Togni; Nicolas Vuilleumier; François Girardin; Francesco Negro; Laurent Gétaz (Journal of Tropical Medicine)
In Swiss prisons, more than 70% of detained people are foreigners and over one-third originate from sub-Saharan Africa or Latin America. These two regions are endemic for various tropical diseases and viral infections, which persist after migration to nonendemic countries. Parasitic infections (schistosomiasis; strongyloidiasis) and cooccurrent viral infections (HIV, hepatitis B (HBV), and hepatitis C (HCV)) are especially of concern for clinical care but have been neglected in empirical research. These diseases often remain silent for years before causing complications, especially if they occur concomitantly. Our research aimed to study the prevalence rates and coinfections of two neglected tropical diseases, namely, Strongyloides stercoralis and Schistosoma sp. and viral infections among sub-Saharan Africans (SSA) and Latin Americans (LA) in Switzerland’s largest pretrial prison. We carried out a cross-sectional prevalence study using a standardized questionnaire and serological testing. Among the 201 participants, 85.6% were SSA and 14.4% LA. We found the following prevalence ratios: 3.5% of HIV (4.1% in SSA, 0% in LA), 12.4% of chronic HBV (14.5% in SSA, 0% in LA), 2.0% of viraemic HCV (1.7% in SSA, 3.4% in LA), and 8.0% of strongyloidiasis (8.1% in SSA, 6.9% in LA). The serological prevalence of schistosomiasis among SSA was 20.3% (not endemic in Latin America). Two infections were simultaneously detected in SSA: 4.7% were coinfected with schistosomiasis and chronic HBV. Four other coinfections were detected among SSA: schistosomiasis-HIV, HIV-chronic HBV, HIV-HCV, and schistosomiasis-strongyloidiasis. To conclude, the high prevalence rates of persistent viral and parasitic infections and their potential coinfections among SSA and LA detained migrants highlight the need to implement control strategies and programs that reach people in detention centers in nonendemic countries.